Marx, Lenin, and the revolutionary experience :studies of communism and radicalism in the age of globalization - Le Blanc, Paul (Routledge, 2006)
Marx, Lenin, and the Revolutionary Experience offers a fresh look at Communism, both the bad and good, and also touches on anarchism, Christian theory, conservatism, liberalism, Marxism, and more, to argue for the enduring relevance of Karl Marx, and V.I. Lenin as democratic revolutionaries. It examines the "Red Decade" of the 1930s and the civil rights movement and the New Left of the 1960s in the United States as well.